2022
DOI: 10.1007/s00420-022-01933-w
|View full text |Cite
|
Sign up to set email alerts
|

Changes in work-related stressors before and during the COVID-19 pandemic: differences by gender and parental status

Abstract: Purpose The COVID-19 pandemic changed people’s working conditions worldwide and research suggests increases in work stressors. However, it is not known to what extent these changes differ by gender or parental status. In the present study, we investigate trends in work stressors and whether these differ by gender and parental status. Methods We used cross-sectional time series data of the European Working Conditions Survey of 2015 and Living, Working and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The qualitative meaning of the response categories was used to determine the cut-off, where categories 1 through 3 have a positive connotation to health and 4 through 5 have a negative. The models were adjusted for gender, age, and educational level, which we assumed would be factors influencing work stress, based on previous studies [16,18,20]. To allow for assessment of each variable's effect on the model, a stepwise approach was used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The qualitative meaning of the response categories was used to determine the cut-off, where categories 1 through 3 have a positive connotation to health and 4 through 5 have a negative. The models were adjusted for gender, age, and educational level, which we assumed would be factors influencing work stress, based on previous studies [16,18,20]. To allow for assessment of each variable's effect on the model, a stepwise approach was used.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding gender, women are more likely than men to experience mental health problems due to work-related stress [17]. Men and women have different exposures to stressors, and research from the COVID-19 period demonstrated increased stressors for women and mothers in terms of work-life conflict [18]. However, a recent metaanalysis showed no support for gender differences in the experience of work-related stress [19], suggesting that the type of occupation and gender balance at the workplace need further investigation as moderating factors.…”
Section: Introductionmentioning
confidence: 99%